The Concept Of Optimal Workplace In Providing A Great Experience To Improve Work Professionalism In The Interior Design Of Pln Corporate University, Ragunan, Jakarta - et al., Asep Yudi Permana (International Journal of Advanced Science and Technology, 2020)
PLN Corporate University is one of the facilities established by PLN Inc. to develop the potentials of subsidiaries and educate employees to gain competence and professionalism. One of its roles is to balance the company’s needs with learning activities using an integrated information system. PLN Corporate University acts as a medium in enhancing excellence in the areas of leadership, competence, and high work ethics. To make it happen, it needs to be supported by spatial planning which supports the work performance and productivity of all employees. Thus, PLN Corporate University needs an office concept which emphasizes on promoting sustainability and on understanding work activities which are more flexible, dynamic, and interconnected, among office spaces, technology, and functions. An office with good characteristics is not only feasible but also able to stimulate the employees to achieve accomplishments in accordance with the employees’ potentials. The development of building and information technology has a major influence on human activities in a space, where offices not only fulfill the need to work, but also have other advantages, such as providing the improved environmental quality and work quality, stimulating the interaction and teamwork among staffs and departments, and encouraging the emergence of innovation through creative processes that occur at the work environment. To achieve the desired condition, the basic concepts applied in the interior design of PLN Corporate University are open-space, flexible, simple, inspiring, performing, phenomenal, and creative in order to realize its vision and mission as the center of excellence in learning.